Implementasi Model Project-Based Learning dalam Pembelajaran Tari Kreasi Kelas XI SMA Negeri 14 Semarang - Marissa Widya Rahma; Utami Arsih (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to describe the implementation of the Project-Based Learning (PjBL) model in creative dance learning. It also analyzes the results of creative dance projects produced by grade XI students of SMA Negeri 14 Semarang. This study uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research subjects consist of one Cultural Arts teacher and students of grade XI. Data analysis employs the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The results show that the implementation of PjBL is conducted through seven systematic stages: project determination, planning, scheduling, exploration and movement creation, monitoring, project presentation, and reflection. Students demonstrate active involvement in group discussions, movement exploration, and collaboration. Each group successfully produces creative dance work with diverse themes, reflecting the development of creativity and critical thinking skills. This study highlights students creative processes at each stage of the project, which has not been widely explored in previous studies.